Development and validation of an interview guide for examining the effects of sports careers on the quality of life of retired Portuguese football players - Teixeira, Eduardo; Silva, Carlos; Vicente, António (Frontiers in Psychology, 2024)
Considering the importance of assessing the impacts resulting from a sport career, this study aimed at developing and validating a semi-structure interview guide suitable for quantifying the sociodemographic and epidemiological profile of former professional football players. Based on the theoretical frameworks and several methodological procedures, an interview guide was developed, consisting of 3 areas of conceptual organization (A1. Biographical data; A2. Professional Career; and A3. Post-Career Transition) and 8 data collection categories (C1. Personal data; C2. Professional data; C3. Sociodemographic background; C4. Epidemiological pathway; C5. Moment of career retirement (career transition); C6. Post-career sociodemographic pathway; C7. Post-career epidemiological pathway; and C8. Perceptions of post-career planning). Thus, in procedural terms, four stages were considered for the construction and validation of the interview guide, namely the Ad hoc construction of the interview guide (i), the review of the interview guide by a panel of experts (ii), definition of procedures and protocol for the application of the interview (iii), and the application of the pilot study for the face validation of the interview guide (iv). The sample consisted of two former Portuguese professional players. To analyze and discuss the data, a content analysis was carried out on all the answers given to each question in the script by the interviewees. From them, matrices were created with the response references to each subcategory. In this way, it was possible to analyse the type of answers given by the interviewees and relate them to the theoretical perspectives of the topic being investigated.The results showed that the interview guide for the study of the impacts of the sports careers on the quality of life of Portuguese former football players shows reliability for the collection of qualitative and quantitative information from the respective content analysis. The use of the interview guide characterizes the path of former player, providing information and knowledge on the sociodemographic and epidemiological impact factors resulting from their post-career.